The Arctic defense postures in the context of the Russia-West confrontation - Andrei V. Zagorski (Arctic and North, 2018)
In 2015–2017, in most Arctic countries, a planned review of defense policy was carried out. It coincided with the Ukrainian crisis, the aggravation of relations between Russia and the West and the active phase of the implementation of a large-scale program of military construction in the Russian Arctic. An analysis of the decisions made during this period allows us to judge to what extent the confrontation between Russia and the West has affected the military and political situation in the region and how it can affect it in the foreseeable future. For this purpose, the documents of the strategic military-political planning of the Arctic countries adopted in recent years are compared with their earlier plans for military construction in the Arctic. The analysis allows to conclude with a high degree of certainty that in the short term the military and political situation in the region will remain stable and predictable. The Arctic countries have not reconsidered their previous calm assessments of military threats and modest military development programs in the region. The main attention of the Arctic states - members of NATO is concentrated on the Arctic not that much as it is for the development of the military-political situation in the Baltic and in the North Atlantic. However, the longer the current crisis in the relations between Russia and the West goes on, the more likely that in the medium and long-term perspective, the military and political situation in the Arctic will change for the worse.